K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

26 tháng 2

x là số tự nhiên à bạn

22 giờ trước (12:55)

To solve the equation ∣x−10∣10+∣x−11∣11=1|x − 10|^{10} + |x - 11|^{11} = 1, we can start by examining the properties of the absolute value function and the exponents.

  1. Case 1: x=10x = 10
    • Substituting x=10x = 10, we have:
∣10−10∣10+∣10−11∣11=0+1=1|10 - 10|^{10} + |10 - 11|^{11} = 0 + 1 = 1

This satisfies the equation, so x=10x = 10 is a solution.

  1. Case 2: x=11x = 11
    • Substituting x=11x = 11, we have:
∣11−10∣10+∣11−11∣11=1+0=1|11 - 10|^{10} + |11 - 11|^{11} = 1 + 0 = 1

This satisfies the equation, so x=11x = 11 is another solution.

For any other value of xx between 10 and 11, the term ∣x−10∣10|x - 10|^{10} and ∣x−11∣11|x - 11|^{11} will not sum to 1 because both terms will be positive and greater than zero, making the sum greater than 1. Outside the range of 10 to 11, one of the terms will be raised to a very high power, making the sum exceed 1.

Therefore, the solutions to the equation ∣x−10∣10+∣x−11∣11=1|x - 10|^{10} + |x - 11|^{11} = 1 are:

x=10x = 10

\

2 tháng 3 2017

10 hoặc 11

2 tháng 3 2017

trình bày nx bn

25 tháng 1 2017

a) \(\frac{x+1}{3}=\frac{x-2}{4}\)

=> (x+1).4 = (x - 2) . 3

=> 4x + 4 = 3x - 6

=> 4x - 3x = - 6 - 4

=> x = - 10

b) \(\frac{x-6}{7}+\frac{x-7}{8}+\frac{x-8}{9}=\frac{x-9}{10}+\frac{x-10}{11}+\frac{x-11}{12}\)

\(\Rightarrow\left(\frac{x-6}{7}+1\right)+\left(\frac{x-7}{8}+1\right)+\left(\frac{x-8}{9}+1\right)=\left(\frac{x-9}{10}+1\right)+\left(\frac{x-10}{11}+1\right)+\left(\frac{x-11}{12}+1\right)\)

\(\Rightarrow\frac{x+1}{7}+\frac{x+1}{8}+\frac{x+1}{9}=\frac{x+1}{10}+\frac{x+1}{11}+\frac{x+1}{12}\)

\(\Rightarrow\frac{x+1}{7}+\frac{x+1}{8}+\frac{x+1}{9}-\frac{x+1}{10}-\frac{x+1}{11}-\frac{x+1}{12}\) = 0

\(\Rightarrow\left(x+1\right).\left(\frac{1}{7}+\frac{1}{8}+\frac{1}{9}-\frac{1}{10}-\frac{1}{11}-\frac{1}{12}\right)\)

\(\frac{1}{7}+\frac{1}{8}+\frac{1}{9}-\frac{1}{10}-\frac{1}{11}-\frac{1}{12}\ne0\) nên x + 1 =0

=> x = -1

c) Xem lại đề

26 tháng 1 2017

Xin ỗi bạn nha! Đoạn x+3 sửa lại thành x+32 nha bạn !!!

5 tháng 6 2019

#)Giải :

a) x + 2x + 3x + ... + 100x = - 213

=> 100x + ( 2 + 3 + 4 + ... + 100 ) = - 213 

=> 100x + 5049 = - 213 

<=> 100x = - 5262

<=> x = - 52,62

5 tháng 6 2019

#)Giải :

b) \(\frac{1}{2}x-\frac{1}{3}=\frac{1}{4}x-\frac{1}{6}\)

\(\Rightarrow\frac{1}{2}x+\frac{1}{4}x=\frac{1}{3}+\frac{1}{6}\)

\(\Rightarrow\frac{1}{2}x+\frac{1}{4}x=\frac{1}{2}\)

\(\Rightarrow\left(\frac{1}{2}+\frac{1}{4}\right)x=\frac{1}{2}\)

\(\Rightarrow\frac{3}{4}x=\frac{1}{2}\)

\(\Leftrightarrow x=\frac{2}{3}\)

Bài làm

     \(\frac{11}{15}-\frac{9}{10}< x< \frac{11}{15}:\frac{9}{10}\)

\(\Rightarrow\frac{22}{30}-\frac{27}{30}< x< \frac{11}{15}.\frac{10}{9}\)

\(\Rightarrow-\frac{5}{30}< x< \frac{11}{3}.\frac{2}{9}\)

\(\Rightarrow-\frac{5}{30}< x< \frac{22}{27}\)

\(\Rightarrow x\in\left\{-4;-3;-2;-1;0;1;2;3;4;5;6;7;8;9;10;11;12;13;14;15;16;17;18;19;20;21\right\}\)

Vậy \(x\in\left\{-4;-3;-2;-1;0;1;2;3;4;5;6;7;8;9;10;11;12;13;14;15;16;17;18;19;20;21\right\}\)

~ Chắc z ~

# Chúc bạn học tốt #

Ta có:\(\frac{11}{15}-\frac{9}{10}< x< \frac{11}{15}:\frac{9}{10}\)

\(\Leftrightarrow\frac{110-135}{30}< x< \frac{11.10}{15.9}\)

    \(\Leftrightarrow\frac{-15}{30}< x< \frac{22}{27}\)

(Vì x c Z)\(\Leftrightarrow-1< x< 1\Rightarrow x\in\left\{0\right\}\)

21 tháng 8 2016

\(\frac{x+2}{10^{10}}+\frac{x+2}{11^{11}}=\frac{x +2}{12^{12}}+\frac{x+2}{13^{13}}\)

\(\Leftrightarrow\frac{x+2}{10^{10}}+\frac{x+2}{11^{11}}-\left(\frac{x+2}{12^{12}}+\frac{x+2}{13^{13}}\right)=0\)

\(\Leftrightarrow\frac{x+2}{10^{10}}+\frac{x+2}{11^{11}}-\frac{x+2}{12^{12}}-\frac{x+2}{13^{13}}=0\)

\(\Leftrightarrow\left(x+2\right).\left(\frac{1}{10^{10}}+\frac{1}{11^{11}}+\frac{1}{12^{12}}+\frac{1}{13^{13}}\right)=0\)

Vì \(\left(\frac{1}{10^{10}}+\frac{1}{11^{11}}+\frac{1}{12^{12}}+\frac{1}{13^{13}}\right)\ne0\)nên \(x+2=0\Rightarrow x=-2\)

21 tháng 8 2016

<=>\(\frac{x+2}{10^{10}}+\frac{x+2}{11^{11}}-\frac{x+2}{12^{12}}-\frac{x+2}{13^{13}}=0\)

<=>\(\left(x+2\right)\left(\frac{1}{10^{10}}+\frac{1}{11^{11}}-\frac{1}{12^{12}}-\frac{1}{13^{13}}\right)=0\)

Vì \(\frac{1}{10^{10}}+\frac{1}{11^{11}}-\frac{1}{12^{12}}-\frac{1}{13^{13}}>0\)

=>  \(x+2=0\)

<=>\(x=-2\)

23 tháng 7 2016

\(\frac{x}{10}=\frac{y}{6}=\frac{z}{21}\)và \(5x+y-2z=28\)

18 tháng 12 2016

\(\frac{x+2}{10^{10}}+\frac{x+2}{11^{11}}=\frac{x+2}{12^{12}}+\frac{x+2}{13^{13}}\)

\(\Rightarrow\frac{x+2}{10^{10}}+\frac{x+2}{11^{11}}-\frac{x+2}{12^{12}}-\frac{x+2}{13^{13}}=0\)

\(\Rightarrow\left(x+2\right)\left(\frac{1}{10^{10}}+\frac{1}{11^{11}}-\frac{1}{12^{12}}-\frac{1}{13^{13}}\right)=0\)

\(\left(\frac{1}{10^{10}}+\frac{1}{11^{11}}-\frac{1}{12^{12}}-\frac{1}{13^{13}}\right)\ne0\Rightarrow x+2=0\)

\(\Rightarrow x=-2\)